Communicative Of Future Educators Innovation in the Formation of Competence Psychological and Pedagogical Possibilities of the Approach - Abdullaev U (Genius Journals, 2022)
The article deals with the psycho-pedagogical aspects of innovative approaches to the formation of communicative competence of future teachers
Keywords: active socio-psychological education; discursive technology of communication; interactive technologies; communicative competence